PELAKSANAAN ZAKAT PERKEBUNAN BUAH LANGSAT DI DESA PUNGGUR KECIL KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Siti Zuleha (CBJIS: Cross-Border Journal of Islamic Studies, 2023)
The aim of this research is to find out and analyze the challenges and obstacles to implementing zakat from langsat fruit plantations in Punggur Kecil Village, Sungai Kakap District and to find out and analyze efforts to increase the implementation of zakat on langsat fruit plantations in Punggur Kecil Village, Sungai Kakap District, Kubu Raya Regency. This research method uses qualitative with a descriptive approach. This research is located in Punggur Kecil Village, Sungai Kakap District, Kubu Raya Regency. Those who were directly involved as primary data sources here were respondents consisting of the Head of Pungur Kecil Village, Religious Figures, Mosque Administrators, Langsat fruit farmers in Punggur Kecil Village, and the Head of Baitulmal Indonesia Munzalan in Punggur Kecil Village, sources who directly provided data to data collector. Secondary data sources here are journal data, theses, books, the internet, information from the local community, as well as other data that supports this research related to zakat, especially zakat from langsat fruit plantations. The research results show: Lack of public knowledge about the obligations and procedures for paying plantation zakat; The level of public awareness is still low; There are differences of opinion regarding the obligation to pay zakat on langsat fruit plantations; The role of the Amil Zakat Institution (LAZ) is not yet optimal; making several efforts to increase the professionalism of zakat organizing institutions in local villages, transparent and targeted distribution of zakat funds by zakat organizers, unifying perceptions regarding zakat law on langsat fruit plantations, creating empowerment programs so that the distribution of zakat on plantations is not only consumptive but can become zakat productive. ongoing socialization and education, both from zakat institutions to the community and local religious leaders.